Effects of protein incorporation on calcium phosphate coating - Leonor, I. B. (2009)
The incorporation of proteins into calcium phosphate (Ca–P) coatings is expected to alter their properties. The aim of this work is, therefore, to study the effect of protein concentration on the formation of Ca–P film. A biodegradable blend of corn starch/ethylene vinyl alcohol (SEVA-C) was used as substrate and bioactive glass (45S5 Bioglass®) was used as a nucleating agent. Bovine serum albumin (BSA) and α-amylase were added, separately, at a concentration of 0.5, 1, and 5 mg/mLto simulated body fluid (SBF) solutions, at the nucleation stage. The incorporation of protein molecules was shown to affect the properties of Ca–P coatings in terms of morphology, composition and crystallinity. Both proteins seem to inhibit in some extent and/or retard the growth of Ca–P nuclei at 0.5 and 5 mg/mL concentrations. FTIR analyses revealed the presence of phosphate and carbonate groups, confiming the formation of a Ca–P layer. The characteristic groups of protein molecules were also detected on the IR spectra, which indicate the efficient incorporation of the proteins into the coatings. When α-amylase was added to the SBF solution the production of reducing sugars was detected, proving the retention of enzyme activity. These results suggest the carrier potential of Ca–P coatings for the sustained delivery of other biologically active proteins and consequently with a strong potential for inducing bone tissue regeneration.